The reform of the EU economic governance framework, market discipline and the role of the ECB - Clemens Fuest (EconPol Forum, 2023)
Experience with European fiscal rules has shown that European rules cannot prevent member states from accumulating high debt levels if they want to. The fact that the ECB increasingly positions itself as a fiscal bailout mechanism implies that the risk of short-term fiscal crises due to a collapse of confidence in capital market declines. But this comes at the cost of further weakening incentives for fiscal discipline- A reform of economic governance should place emphasis on enhancing fiscal discipline and responsibility. The proposal that an excessive deficit procedure will be opened by default if countries deviate from their agreed fiscal adjustment paths may improve discipline. In contrast, the idea to allow countries to incur more debt if their policies are aligned with EU political priorities will weaken fiscal discipline
Keywords: 330